(untitled) (Bangladesh Journal of Endosurgery, 2014)
Introduction: Anomalies of midgut rotation and fixation associated with volvulus and vascular compromise require urgent surgical intervention. Recent literature supports laparoscopic management of intestinal malrotation in children. But conversion and complication rates of laparoscopic treatment are higher, especially in neonates, and when associated volvulus and bowel ischemia are present. The authors present their experience and results of laparoscopic management of uncomplicated cases of intestinal malrotation in children excluding newborns. Methods: A retrospective analysis of all the children who underwent elective laparoscopic Ladds (LL) procedure was done. All neonates and children presenting with signs of acute volvulus and bowel ischemia were excluded from LL procedure. Between April 2007 and April 2013, 12 patients underwent LL procedure at the authors institution. Of the 12 patients, 8 were boys and the age ranged from 3 months to 9 years. All patients were presented with symptoms of abdominal pain and intermittent bilious vomiting. Diagnosis of intestinal malrotation was suggested either by Doppler ultrasonography or upper gastrointestinal contrast study and confirmed by diagnostic laparoscopy in all the patients. A standard Ladds procedure with appendectomy was performed laparoscopically in all cases. Results: All procedures were completed laparoscopically. Average duration of procedure was about 95 min (75130 min). Feeding was started on post-op day 1 and all patients were discharged by day 4. There were no immediate or early postoperative complications, but one patient developed intestinal obstruction on follow-up and required intervention. All patients are doing well on latest follow-up. Conclusion: LL procedure can be successfully performed in infants and children with uncomplicated cases of intestinal malrotation. Conversion rates are negligible and complications are minimal if strict selection criteria are followed. DOI: http://dx.doi.org/10.11593/bje.2013.0103.0017 Bangladesh Journal of Endosurgery Vol.1(3) September 2013: 1-5